Phoenix Dactylifera Accelerates Duration The Active Phase of The First Stage of Labor: A Quasi Experiment - Kundarti, Finta Isti; Titisari, Ira; Rahayu, Dwi Estuning; Susatia, Budi; Nurlaili, Anis (Research and Community Service Unit, Poltekkes Kemenkes Kupang, 2025)
Cases of prolonged labor in women in the world are still quite high. Inadequate uterine contractions are the main cause of complications in women's deaths worldwide. The aim of this study was to determine the effect of Phoenix Dactylifera on the length of labor in the active phase of the first stage. This research was carried out through a Quasi-Experimental design Quasi-Experimental. The 60 participants were divided into 2 groups, the intervention group (30 participants) and control (30 participants) at the Kediri Regency Health Center. Sampling uses simple random sampling. The intervention group was given 70 grams of phoenix dactylifera fruit daily from 37 weeks of gestation until labor, while the control group was given standard care. The results of the Paired t-test, the average length of labor in the first stage of the active phase in the intervension group (m=90.57, SD=56.507) p-value 0.000, and the control group (m= 271.33, SD=151.361) p-value 0.100. The difference in the average of the two groups is tested using an independent t-test. The difference in mean length of labor in the first stage of the active phase posttest in the intervention vs. the control group (m=90.57, SD=56.507vs m=271.33, SD=151.361) p-value 0.000. The difference in length of labor in the first stage of the active phase in the two groups was 180.76 minutes/ (3 hours 36 minutes). The Phoenix Dactylifera can shorten duration of the active phase of labor in the first stage of labor. It is recommended for health workers to give phoenix Dactylifera at the right dose to pregnant women in the third trimester to increase stamina during pregnancy and good uterine contractions.